2018
DOI: 10.1111/1756-185x.13267
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate might reduce ischemic stroke in patients with rheumatoid arthritis: a population‐based retrospective cohort study

Abstract: At a dosage of > 0.5 defined daily dose, short-term methotrexate might decrease ischemic stroke risk in RA patients, while hydroxychloroquine and sulfasalazine were neutral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
(25 reference statements)
1
17
0
Order By: Relevance
“…Our finding that non-AF RA patients with a CHA 2 DS 2 -VASc score of ≥2 had a higher risk of ischemic stroke is similar to the case of systemic lupus erythematosus patients without AF [25]. Previous studies have also demonstrated an increased risk of ischemic stroke 10 or more years after RA diagnosis [3,4,41]. This result was also observed in our study, especially in patients with a higher CHA 2 DS 2 -VASc score (≥2).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our finding that non-AF RA patients with a CHA 2 DS 2 -VASc score of ≥2 had a higher risk of ischemic stroke is similar to the case of systemic lupus erythematosus patients without AF [25]. Previous studies have also demonstrated an increased risk of ischemic stroke 10 or more years after RA diagnosis [3,4,41]. This result was also observed in our study, especially in patients with a higher CHA 2 DS 2 -VASc score (≥2).…”
Section: Discussionsupporting
confidence: 88%
“…Rheumatoid arthritis (RA) is one of the most prevalent chronic inflammatory polyarthritis with a prevalence of 0.5-1% with female predominance in industrialized countries [1]. The risk of stroke is higher in patients with RA compared with the general population or patients with noninflammatory arthropathies [2][3][4][5]. Patients with RA are also at a higher risk for long-term disability after stroke [6].…”
Section: Introductionmentioning
confidence: 99%
“…HCQ use is associated with lower low-density lipoprotein levels but not carotid artery intima media thickness in lupus nephritis patients [31]. Hydroxychloroquine has no significant protective effect on ischemic stroke in rheumatoid arthritis patients [32]. Whether HCQ therapy in SLE decreases risk of stroke is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…102 Low-dose methotrexate was not effective in reducing stroke risk prospectively, 103 though retrospective data indicate chronic use in rheumatoid arthritis is associated with a reduced rate of ischemic stroke. 104 With IL-6 positioned as a key regulator of virus-associated cerebrovascular events, these therapies could prove beneficial in preventing virally-mediated stroke. The anti-gout medication, colchicine can also reduce IL-6 levels and may have benefit in treating cardiovascular disease including reducing ischemic stroke rates.…”
Section: Therapeutic Strategies To Target Sars-cov-2 Action In the Cerebral Vasculaturementioning
confidence: 99%